Accountability Challenges in the Transnational Regime Complex for Climate Change. Issue 1 (30th November 2016) - Widerberg, Oscar; Pattberg, Philipp
Abstract: This article discusses challenges to accountability in the context of transnational climate governance. It argues that the emergence of a distinct transnational regime complex and the increasingly integrated structure of international and transnational climate governance create new challenges for using established analytical frameworks that rely on accountability regimes for individual actor types. Instead, studying accountability requires a system‐level conceptualization and a revisiting of accountability regimes, taking diversity and networked governance structures into account. Using data from the CONNECT‐project on the transnational regime complex for climate change, the article uses a framework of six elements of an accountability regime to identify three overarching accountability challenges. First, the expanding borders of the transnational regime complex for climate change are starting to shift accountability from the multilateral level (the UNFCCC) to a networked and more intricate structure. Second, transparency, monitoring, and reporting remain an urgent challenge despite a rapidly increasing flow of data and repositories in particular concerning ex‐post impacts. Third, the availability and utility of sanctions are poorly understood in the context of transnational climate governance.